2017
DOI: 10.1097/wad.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Successful Lumbar Puncture in Alzheimer Research

Abstract: Objective Lumbar puncture (LP) is increasingly common in Alzheimer disease research; however, agreement to undergo LP varies. We sought to determine factors influencing LP consent at Alzheimer’s Disease Centers (ADCs) in the United States. Methods A three-part survey was distributed to each ADC: 1) ADC LP Experience; 2) LP Requestor Experience; and 3) Patient LP Experience (both Initial and Follow-up). 64 LP Requestor, 579 Patient/Initial, and 404 Patient/Follow-up surveys were collected. Logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Most fluid biomarkers that have proven valuable for the diagnosis or monitoring of AD have been measured in CSF. Lumbar puncture, which is necessary to obtain CSF, is generally safe and well tolerated; however, it is time consuming and sometimes results in postpuncture headache and other side effects 97 . There are increasing efforts to develop easily assessable fluid biomarkers (e.g., from peripheral sources).…”
Section: Readily Accessible Blood Biomarkersmentioning
confidence: 99%
“…Most fluid biomarkers that have proven valuable for the diagnosis or monitoring of AD have been measured in CSF. Lumbar puncture, which is necessary to obtain CSF, is generally safe and well tolerated; however, it is time consuming and sometimes results in postpuncture headache and other side effects 97 . There are increasing efforts to develop easily assessable fluid biomarkers (e.g., from peripheral sources).…”
Section: Readily Accessible Blood Biomarkersmentioning
confidence: 99%
“…Among studies evaluating V, a significant association with PDPH was identified by 4/14 (28.5%) . An increased volume of CSF withdrawal was associated with either reduced PDPH risk by 2/4 (50%), or increased PDPH risk in 1 study . Finally, Monserrate demonstrated an increased risk with either high or low volume removal, depending on the timing of the outcome .…”
Section: Resultsmentioning
confidence: 97%
“…Manual review of abstracts and/or full texts identified 22 unique references evaluating the relationship between CSF volume and/or pressure measurements and PDPH incidence (Fig. ) . The references included analysis of V (n = 14), OP (n = 11) and/or CP (n = 4) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations